2020
DOI: 10.3390/nu12040934
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Obesity on Human Milk Macronutrient Composition: A Systematic Review and Meta-Analysis

Abstract: Maternal obesity has been associated with changes in the macronutrient concentration of human milk (HM), which have the potential to promote weight gain and increase the long-term risk of obesity in the infant. This article aimed to provide a synthesis of studies evaluating the effects of maternal overweight and obesity on the concentrations of macronutrients in HM. EMBASE, MEDLINE/PubMed, Cochrane Library, Scopus, Web of Science, and ProQuest databases were searched for relevant articles. Two authors conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 62 publications
(126 reference statements)
8
55
2
2
Order By: Relevance
“…What is more, our findings showed an association between current BMI, maternal body composition during breastfeeding and infant sex and the macronutrient concentration in mature HM, collected 1–2 months postpartum. Similar to other studies [ 16 ], our data show that fat concentration in HM was positively correlated with maternal nutritional status. However, our study provides better insight by assessing nutritional status not only with BMI value, but mainly with body composition analysis and analyzing milk samples from a 24-h period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…What is more, our findings showed an association between current BMI, maternal body composition during breastfeeding and infant sex and the macronutrient concentration in mature HM, collected 1–2 months postpartum. Similar to other studies [ 16 ], our data show that fat concentration in HM was positively correlated with maternal nutritional status. However, our study provides better insight by assessing nutritional status not only with BMI value, but mainly with body composition analysis and analyzing milk samples from a 24-h period.…”
Section: Discussionsupporting
confidence: 91%
“…Chang et al [ 35 ] observed that women’s current BMI was positively correlated with fat concentration in HM at early (1–2 weeks) and late (7–8 months) lactation stages. However, Leghi et al [ 16 ] reported in their meta-analysis that the fat concentration in transitional milk showed an inverse correlation. Simultaneously, no impact of maternal overweight or obesity on fat concentration in colostrum was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is known that the gut microbiome composition differs in healthy and obese people; therefore, an aberrant microbiome can be vertically transmitted from an obese mother to her infant. Mother-to-newborn transmission of microbiota might be a causal factor underlying obesity’s transmission [ 91 , 92 ].…”
Section: Human Milk: a Contribution To The Development Of Infant Gmentioning
confidence: 99%
“…Maternal obesity and maternal atopy are highly prevalent states that may have an effect on HM composition and infants' health outcomes (9)(10)(11)(12)(13)(14). Few studies, however, have attempted to evaluate associations between HM metabolome composition and measures of infants' health and development.…”
Section: Early Life Nutrition and Health Outcomes In Later Lifementioning
confidence: 99%